Is full harmonization of laws with regard to artificial intelligence possible? - Augustyn-Skuza, Paulina (Studia Iuridica Toruniensia, 2024)
The article addresses the issue of full harmonization of laws on artificial intelligence. The need for legal regulations for artificial intelligence is not in doubt, but there are a number of questions at what level these regulations should be introduced. Creating a unified legal practice for artificial intelligence requires cooperation between state governments, technology developers, experts and lawyers. This coordination is key to creating effective legislation. The text is centered around the EU framework. Given the dynamic nature of artificial intelligence and its rapid development, legal regulations should be flexible and adaptable to ongoing changes.